Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) X. The commotica species-group, with descriptions of twenty-two new species - Wang, Shuxia; Liu, Chen (Zootaxa, 2021)
The commotica species-group of the genus Promalactis Meyrick, 1908 is proposed based on forewing pattern. Moths of this species group are characterized by the possession of three white streaks extending from the dorsum of the forewing. Twenty-two new species are described herein: P. apiculifera sp. nov., P. apisetosa sp. nov., P. arcicosta sp. nov., P. baoshana sp. nov., P. bicornuta sp. nov., P. bilobignatha sp. nov., P. binipapillata sp. nov., P. bispina sp. nov., P. curvicosta sp. nov., P. denticuligera sp. nov., P. lianhuashana sp. nov., P. motuoensis sp. nov., P. pedata sp. nov., P. quadriprocessa sp. nov., P. ramiformis sp. nov., P. senticosa sp. nov., P. similibellatula sp. nov., P. squamacea sp. nov., P. stenognatha sp. nov., P. subgladiata sp. nov., P. tengchongensis sp. nov. and P. triangulivalva sp. nov. The female of P. spinosicornuta Du & Wang, 2013 is described for the first time. Photographs of adults and genitalia of the new species are provided. A list of all the species belonging to the commotica species group is given.